ACE Membership: A Benchmark Study - Judith McIntosh White; Gary J. Wingenbach (Journal of Applied Communications, 2007)
This study continues inquiry into the reasons people join and retain membership in voluntary professional organizations. Expanding on a study of historical membership data (1991-2004) provided by the Association for Communication Excellence in Agriculture, Natural Resources, and Life and Human Sciences (ACE), 555 individuals who were dues-paying ACE members in 2006 were sent online surveys. Methodology was based on Dillman's Tailored Design Method. Sixty-four percent of the population responded. Analysis indicated that members were a fairly homogeneous group in terms of employment classification and regional membership status. Average membership tenure was 3.34 years, with 27% of members reporting a lapse in membership. Respondents valued and were satisfied with organizational communication, professional development opportunities, publications, networking, and annual meetings. However, they expressed dissatisfaction with some organizational components, including special interest groups, "cliquishness," lack of diversity, features of the annual meeting, and judging in the awards program. The findings support existing literature about workplace organizational loyalty and commitment and the extended application of such studies to voluntary organizations.